FACTORS INFLUENCING AIS CAPABILITY AND PERFORMANCE OF MALAYSIAN CO-OPERATIVES: A CONCEPTUAL FRAMEWORK - Mohd Hadzrami Harun Rasit; Mohammad Azhar Ibrahim (International Journal of Accounting, Finance and Business, 2018)
Accounting information systems (AIS) capability is important because it involves the ability of AIS to process business data into useful information according to user requirements. Indeed, empirical evidences suggested that the use of AIS has positive impact on firm performance. However, factors that contribute to building AIS capability which in turn improve firm performance were not adequately explained. As such, this paper draws on the resource-based view (RBV) to define various dimensions of information systems (IS) resources. Previous studies were concentrating on small and medium-sized enterprises (SMEs) and public listed companies leaving a gap in co-operatives literatures. Also, prior studies were focusing on specific AIS capability namely enterprise resources planning (ERP) and dynamic AIS capability using dynamic capabilities framework which is dissimilar from the current study. This paper contributes to the literature by providing a better understanding of the roles of IS resources in capability-building of AIS. This paper also contributes in establishing the AIS capability-building framework within co-operatives environment in Malaysia.